The Melanocortin 3 Receptor: A Novel Mediator of Exercise-Induced Inflammation Reduction in Postmenopausal Women?. (21st December 2010) - Henagan, Tara M.; Phillips, Melody D.; Cheek, Dennis J.; Kirk, K. Michelle; Barbee, James J.; Stewart, Laura K.
Abstract : The purpose of this study was to determine whether resistance exercise training-induced reductions in inflammation are mediated via melanocortin 3 receptor expression in obese (BMI32.7 ± 3.7 ) women (65.6 ± 2.8  yrs) randomized to either a control (N = 11 ) or resistance training group (N = 12 ). The resistance trained group performed resistance training 3 days/week for 12 weeks. Resting blood samples were collected before and after the training intervention in both resistance trained and control groups. Resistance training upregulated melanocortin 3 receptor mRNA by 16-fold (P = .035 ) and decreased monocyte count, without changing leukocyte number, body composition, or body weight. Resistance trained individuals exhibited increased sensitivity to inflammatory stimuli, whereas control individuals exhibited no change. While there was no change in whole blood tumor necrosis factor alpha mRNA between the groups, whole blood interleukin 10 mRNA was higher in the resistance trained group following the intervention period. In summary, it appears that resistance training may modulate melanocortin 3 receptor expression, providing a possible mechanism for the anti-inflammatory effects of exercise training.